TPB–DOI Model of Sustainable Palm Oil Adoption in Indonesia - Denashurya, Nugra Irianta (International Journal of Multidisciplinary Research of Higher Education, 2026)
The palm oil industry plays a pivotal role in Indonesia’s economy and contributes to achieving the United Nations Sustainable Development Goals (SDGs). However, concerns regarding economic, environmental, and social sustainability highlight the urgent need to promote sustainable agricultural practices. This study examines potential challenges in implementing the Indonesian Sustainable Palm Oil (ISPO) certification system in 2025 and develops a comprehensive adoption model by integrating Ajzen’s Theory of Planned Behavior (TPB) and Rogers’ Diffusion of Innovation (DOI). The model incorporates eight factors: attitude, subjective norms, perceived behavioral control, relative advantage, compatibility, complexity, trialability, and observability. Structured questionnaires were administered to 300 independent smallholder palm oil farmers in West Kalimantan, Indonesia, and the data were analyzed using structural equation modeling (SEM). The findings confirm that attitude, subjective norms, perceived behavioral control, relative advantage, compatibility, and trialability positively and significantly influence the adoption of sustainable farming practices, while complexity exerts a significant negative effect. Observability showed no significant impact. These results provide valuable insights for policymakers and practitioners to design targeted strategies, programs, and policies that strengthen social norms, enhance perceived behavioral control, and emphasize the relative advantage and compatibility of sustainable practices. By fostering voluntary adoption among independent smallholders, the successful implementation of ISPO can be ensured, benefiting both farmers and the environment.